Pelatihan Karya Tulis Ilmiah untuk Meningatkan Kompetensi Profesionalisme Guru - Oktavia Liza, Ledya; Zudeta, Effran (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The world of education is required to produce human resources, in this case, teachers who continue to develop in line with technological developments and their professionalism. One of the teacher's demands in the field of professionalism is the publication of scientific papers. The purpose of this research is to provide scientific writing training for Vocational High School teachers. Participants in this training were 13 vocational school teachers. The training is given in 2 sessions, the first session is to offer training on scientific papers, the reasons why teachers have to make scientific papers, the concept of scientific papers, and the process of writing scientific papers. The second session provides an understanding of how to publish scientific papers, writing formats up to sending scientific papers for publication. Writing Scientific Papers to Improve Teacher Professional Competence before and after being given training experienced an increase from 56.5% to 79.6%. Based on this, it can be concluded that training in writing scientific papers can increase teacher professionalism.